Charlson syndrome index predicted survival in pancreatic cancer patients received immunotherapy - Zhang, Nan; Chen, Shiyun; Shi, Yue; Wang, Zhikuan; Jia, Ru; Dai, Guanghai (Frontiers in Immunology, 2025)
ObjectiveThe Charlson Comorbidity Index (CCI) is a widely utilized assessment tool for evaluating the mortality rate among patients with chronic diseases and tumors. Currently, there is a dearth of research investigating the correlation between CCI and survival rates in advanced pancreatic cancer patients received immunotherapy. Therefore, this study aims to elucidate the association between CCI and survival rates in real-world settings for pancreatic cancer patients received immunotherapy.MethodsA total of 104 patients with advanced pancreatic cancer who received immunotherapy at the General Hospital of the People’s Liberation Army between September 2015 and September 2020 were included in this study. The patients were categorized into two groups based on their Charlson Comorbidity Index (CCI) scores: low CCI group (CCI <7) and high CCI group (CCI ≥7). The statistical analysis focused on examining the correlation between CCI score and survival outcome.ResultsThe high CCI group exhibited significantly lower overall survival (OS) and progression-free survival (PFS) compared to the low CCI group (p<0.05). The median OS for the high CCI and low CCI groups were 7.82 and 44.17 months, respectively, while the median PFS were 2.40 and 6.40 months, respectively. Multivariate analysis revealed that high CCI was independently risk factor for both OS (HR=2.801, 95%CI: 1.433-5.472, p=0.003) and PFS (HR=2.546, 95%CI: 1.389-4.668, p=0.003).ConclusionThe CCI score serves as a significant independent predictive indicator for advanced pancreatic cancer patients received immunotherapy.